Moralni vidiki izobraževanja v starem Rimu - Šega-Čeh, Barbara (Keria (Ljubljana), 2000)
The article with a series of quotations of different authors from moral and ethical view elucidates relations to the education in ancient Rome which was, on the first side, spread within the old mores maiorum and, on the other side, influenced by vivacious and fertile Greek creativeness, not always in concord with valid Roman moral norms and ethical principles. On the basis of selected quotations, the article is concluded by hypothesis about one of the reasons for manumission of enslaved Greek pedagogues.
Keywords: antični Rim; izobraževanje; morala; vzgoja